Modelowanie rozprzestrzeniania zanieczyszczeń w powietrzu na przykładzie projektowanej kwatery składowiska odpadów = Simulation of the pollution spreading in the air basis of planned cell for waste - Cuske, Mateusz; Szałata, Łukasz (Zielona Góra: Oficyna Wydawnicza Uniwersytetu Zielonogórskiego)
The paper presents methodological issues and different ways to modeling of pollutants spreading in the air using an Operat FB program. Showed the results of typical emissions from planned cell for waste of landfill. The analyzes showed that the maximum and average concentrations of pollutants are different, depending on the used input data.
Keywords: modelowanie; zanieczyszczenie powietrza; składowisko odpadów; modeling; air pollution; landfill